Activated abscisic acid pathway and C4 pathway, inhibited cell cycle progression, responses of Ulva prolifera to short term high temperature elucidated by multi-omics. (January 2023) - Zhao, Hui; Liu, Xuanhong; Jiang, Ting; Cai, Chuner; Gu, Kai; Liu, Yuling; He, Peimin
Abstract: The annual outbreak of green tides since 2007 has destroyed coastal waters' ecological environment and caused substantial economic losses. Ulva prolifera, known as the dominant species of green tides, is influenced by temperatures. Omics-based technology was used to analyze U. prolifera under 12 h of treatment at 30 °C in the work. High temperature has the following advantages, e.g., activating the abscisic acid signaling pathway, improving the heat tolerance of U. prolifera, up-regulating metabolites such as glycolipids, glyceroyl, and glutamic acid to maintain the stability and fluidity of cells, and reducing the stimulatory effect of external stress on cells. The key genes and proteins of the tricarboxylic acid cycle, glycolysis, and pentose phosphorylation pathways were inhibited; however, the key enzyme pyruvate phospho-dikinase of the C4 pathway was up-regulated. The C4 pathway was activated in U. prolifera in response to high-temperature stress and may play a key role in photosynthesis. Besides, U. prolifera metabolizing amino acids was active. High temperature inhibited genes and proteins related to DNA replication and cell cycle in the transcriptome and proteome as well as the growth and reproduction of U. prolifera . Highlights: Analyzed the response mechanism of Ulva prolifera by omics. The C4 pathway was activated in response to high-temperature stress and may play a key role in photosynthesis. Molecules related to DNA replication, cell cycle, growth and reproduction was inhibited.